Contributing Factors of Carbon Emission Disclosure: Evidence From Transportation Companies In Indonesia - Widiyati, Dian (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the impact of capital expenditures, company age, independent commissioners, and profitability on carbon emission disclosures. This study employs annual reports as its data source, while its analysis unit is an entity sourced from the Indonesia Stock Exchange. The investigation utilized measurements at a single point in time between 2018 and 2020. This study's population comprises transportation-sector companies listed on the Indonesia Stock Exchange within the past three years (2018-2020). The sample selection procedure uses purposive sampling techniques, yielding 45 annual reports as samples. E-Views 10 was used in this study's analysis instruments.  This study concludes that capital expenditure has no effect on carbon emission disclosure (H1 rejected), company age affects carbon emission disclosure (H2 accepted), independent commissioners have no effect (H3 rejected), and profitability has no effect (H4 rejected). Future benefits of carbon emission disclosure necessitate that policymakers develop a policy regarding carbon emissions in light of this finding.